Implementation of Nursing Education on Physical Exercise for Post-Section Caesarean Surgery Patients with Impaired Physical Mobility Problems in the Obstetrics Room at Lahat Regional Hospital - Yeni Elviani; Sri Hartati; Ratna Ningsih; Angita Sakira (PT FORMOSA CENDEKIA GLOBAL, 2023)
The problem of impaired physical mobility in post-cesarean section patients is caused by the presence of surgical scars which cause pain in the patient, so that the patient prefers to lie down and not move. The causes of caesarean section include fetal factors, maternal factors, and birth history. Research Objective: To determine the implementation of maternity nursing care with physical exercise education for post-cesarean section patients with physical mobility problems at Lahat Hospital 2023. Research Method: Descriptive in the form of a case study, with two post-SC clients who have physical mobility problems. The approach used is nursing care which includes assessment, nursing diagnosis, planning, implementation, evaluation and documentation. Research Results: After being given physical exercise education, namely patients 1 and 2, they were able to practice physical exercise independently. Conclusion: The implementation of nursing care with physical exercise education shows the effectiveness of reducing physical mobility disorders in post-SC patients. Exercises There is no charge, and each movement can be completed independently at home